Effect of Seasonal Variation on Some Physio-Chemical Properties of Water of Tigris River in Mosul City. - Eman Al-Sarraj (College of Education for Pure Sciences, 2020)
This study was conducted for some physical and chemical properties by knowing the impact of pollutants of Mosul city, for three selected stations of water along the Tigris River during the seasons of 2018 and 2019. The following field and laboratory tests were carried out: Temperature of water, Turbidity, Electrical conductivity, Dissolved oxygen (DO), Biochemical oxygen demand (BOD5) as well as µmeasuring the concentration of ions for chlorides, orthophosphate, nitrate, and sulfate. The results showed there was a clear fluctuation in all physical and chemical variables with different seasons and geographical location. Water temperature ranged between 14.2-25.5 °C, Turbidity 2.8-23.1 NTU, EC 266-335 µc/cm, PH 7.6-8.5, DO 6.6-9.6 mg/l, BOD5 1.4-2.9 mg/l, TH 130-338 mg/l, CL 9.8-29.9 mg/l, SO4 120-177 mg/l, NO3 0.09-166 mg/l, PO4 0.011-0.036 mg/l. Although, the increasing of all values towards the south of the city, these obtained values were within the limits for local and international standards.